The Attempts Of The Panjalu Community To Preserve The Ngumbah Pusaka Ritual Ceremony In The Era Of Modernization - Annisa Arum Mayang; Aisyah Edy Itsniya; Livia Victoria Senduk (Universitas Tanjungpura, 2023)
Ngumbah Pusaka is one of the cultures owned by the community of Panjalu. In this era of modernization, the Ngumbah Pusaka Ritual has undergone many changes in accordance with human life. The worst thing is the fading of culture and even the disappearance of a culture. This research aims to find out how the Panjalu community preserves the Ngumbah Pusaka ritual ceremony in the era of modernization. This research uses descriptive qualitative method, with data collection techniques through observation, interviews, documentation, and literature study. The rapid development of technology in the modernization era is one of the obstacles to maintaining culture. One of the way to preserve the Ngumbah Pusaka ritual ceremony is by continuing to hold the ritual every year by adapting to the times.